2009
DOI: 10.3390/ijms10020518
|View full text |Cite
|
Sign up to set email alerts
|

Biomass Production Potential of a Wastewater Alga Chlorella vulgaris ARC 1 under Elevated Levels of CO2 and Temperature

Abstract: The growth response of Chlorella vulgaris was studied under varying concentrations of carbon dioxide (ranging from 0.036 to 20%) and temperature (30, 40 and 50°C). The highest chlorophyll concentration (11 μg mL–1) and biomass (210 μg mL–1), which were 60 and 20 times more than that of C. vulgaris at ambient CO2 (0.036%), were recorded at 6% CO2 level. At 16% CO2 level, the concentrations of chlorophyll and biomass values were comparable to those at ambient CO2 but further increases in the CO2 level decreased … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

10
102
3
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 231 publications
(117 citation statements)
references
References 33 publications
10
102
3
2
Order By: Relevance
“…Similar to our study, Chinnasamy et al (2009) protein content (dry weight) was obtained. Our results for protein content in Chu and WC media are about twice higher than those reported by Illman et al (2000), who showed 29% (dry weight) protein production by C. vulgaris in Watanabe medium.…”
Section: Resultssupporting
confidence: 55%
“…Similar to our study, Chinnasamy et al (2009) protein content (dry weight) was obtained. Our results for protein content in Chu and WC media are about twice higher than those reported by Illman et al (2000), who showed 29% (dry weight) protein production by C. vulgaris in Watanabe medium.…”
Section: Resultssupporting
confidence: 55%
“…Previous studies have demonstrated that the biomass and lipid content in some microalgae were affected by various cultivation conditions such as nitrogen supply and its sources (Li et al, 2008;Arumugam et al, 2013), salt concentration (Takagi et al, 2006), level of CO 2 (Chinnasamy et al, 2009), light intensity, and temperature (Renaud et al, 2002;Khotimchenko and Yakovleva, 2005;Juneja et al, 2013). These observations allowed us to hypothesize that there might be a profound effect of media type and carbon sources on the biomass and oil content of the microalgae S. sticticum, T. reflexa, U. elongatum, and C. turgidus.…”
Section: Introductionmentioning
confidence: 99%
“…However, at CO 2 concentrations greater than 6%, Chlorella vulgaris demonstrated a decrease in growth rate with decreasing pH levels. 118 The increase in biomass was observed for protein and carbohydrate, whereas the lipid concentration decreased by 5.8%. 118 This benchtop research demonstrates a useful methodology needed to find the optimal algae growing conditions.…”
mentioning
confidence: 93%
“…118 The increase in biomass was observed for protein and carbohydrate, whereas the lipid concentration decreased by 5.8%. 118 This benchtop research demonstrates a useful methodology needed to find the optimal algae growing conditions. A benchtop study conducted by Francisco et al 119 tested six strains of microalgae in a PBR employing CO 2 sequestration.…”
mentioning
confidence: 93%
See 1 more Smart Citation